2012
DOI: 10.5539/jfr.v1n3p111
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Amaranth Grain-based Nutritious Complementary Foods with Dagaa Fish (Rastrineobola argentea) and Edible Termites (Macrotermes subhylanus) Compared to Corn Soy Blend Plus among Young Children/Mothers Dyads in Western Kenya

Abstract: We assessed acceptability of two flours and porridges of complementary foods based on germinated grain amaranth and maize with or without edible termites and dagaa small fish named "Winfood Classic" (WFC) and "Winfood Lite" (WFL), respectively, compared to Corn Soy Blend Plus (CSB+) among mothers and young children. A total of 57 children consumed each of the three foods on separate days with one-day washout between foods. Each food was considered acceptable if the child consumed at least 75% of the serving. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Some of these studies, however, have heterogeneous baseline participant populations, varying measures of anthropometry, various timing of interventions and some lack appropriate control groups emanating from diverse intervention products and study designs (Admassu et al, ; Arnold et al, ; Bauserman et al, ; Owino et al, ; Skau et al, ) unlike the present study and a similar parallel one in Cambodia (Skau et al, ) which recruited children of similar age, had a control(s), and were conducted in food‐insecure settings. Another strength of the current study is that we evaluated locally available food sources for infant feeding with the developed products being acceptable to mothers and infants (Konyole et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these studies, however, have heterogeneous baseline participant populations, varying measures of anthropometry, various timing of interventions and some lack appropriate control groups emanating from diverse intervention products and study designs (Admassu et al, ; Arnold et al, ; Bauserman et al, ; Owino et al, ; Skau et al, ) unlike the present study and a similar parallel one in Cambodia (Skau et al, ) which recruited children of similar age, had a control(s), and were conducted in food‐insecure settings. Another strength of the current study is that we evaluated locally available food sources for infant feeding with the developed products being acceptable to mothers and infants (Konyole et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Food ingredients used for the complementary foods are already widely available and consumed in the locality (Kinyuru et al, ). Details of recipe formulation, nutrient composition, processing technology, and safety are described elsewhere (Kinyuru et al, ), and the foods were found to be acceptable prior to the intervention in the study population (Konyole et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the heat, pressure and mechanical shear generated during extrusion destroy pathogenic bacteria often associated with insects thus improving the safety. Earlier, Konyole et al (2012) tested the acceptability of amaranth and maize grain-based complementary weaning food enriched with dagaa fish (3%), and edible termites (10%) among young children and their mothers in western Kenya. The product scored similar acceptability as one not enriched with termite.…”
Section: Composite Fortified Foodsmentioning
confidence: 99%
“…In another study, termite‐based foods were just as acceptable to infants and mothers as corn‐soy blend foods (Konyole et al . ) and there were no significant differences in aroma and taste acceptability scores of wheat flour buns enriched with between 0% and 20% of termite flour (Kinyuru et al . ).…”
Section: Introductionmentioning
confidence: 99%